Penerapan quizwhizzer sebagai media pembelajaran berbasis gamifikasi untuk meningkatkan motivasi dan keterlibatan belajar siswa dalam pembelajaran ips di kelas viii - Alfahmi, Wildan (Maliki Interdisciplinary Journal, 2025)
Education Education plays a vital role in enlightening the nation and preparing a competitive generation to face the challenges of the 21st century. In this context, the implementation of gamification in learning has emerged as an innovative solution to enhance students’ motivation and engagement. This study aims to analyze the application of the gamification-based learning media QuizWhizzer in efforts to increase motivation and participation among eighth-grade Social Studies students. The research approach used is qualitative with a case study design to provide an in-depth description of the effectiveness and impact of using QuizWhizzer in the learning process. Data collection techniques included observation, interviews, and documentation. The results indicate that utilizing QuizWhizzer can improve students’ learning motivation through game elements such as leaderboards, avatars, and interactive challenges, which make students more enthusiastic and actively involved in the learning process.